Inspiratory muscle fatigue as an exercise limiting factor - Wüthrich, T. U.; Eberle, E. C.; Spengler, C. M. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Recent studies of cycling time trials (TT) suggest the existence of a threshold for quadriceps muscle fatigue being regulated via feedback from type 3 and 4 afferents of working muscles. In order to avoid surpassing this threshold of fatigue, feedback from working limbs is suggested to directly influence the regulation of exercise intensity (1). Since the diaphragm is also susceptible to fatigue during high-intensity whole-body exercise and owing to its vital role, one would expect it to be even more protected against excessive fatigue. Thus, we hypothesised that a threshold for diaphragm fatigue existed similar to that of the quadriceps muscle. To test this, we assessed diaphragm contractility via transdiaphragmatic twitch pressure (Pdi,tw) in response to cervical magnetic stimulation prior to and following 15- and 30-min running TTs. Additionally, we assessed mouth twitch pressures (Pm,tw) prior to and following exhaustive volitional normocapnic hyperpnoea in 7 well-trained healthy runners with normal lung function (age±SD: 31±5 yrs; VO2max:65.9±3.9 ml/min/kg; FVC: 6.41±0.38 litre; FEV1: 4.83±0.33 litre). Well-trained endurance athletes were investigated for the reason that they are more likely to reach the potential limit of their respiratory system than healthy sedentary subjects due to the specificity of endurance training which mainly increases the capacity of the cardiovascular system and the skeletal muscles to transport and utilize oxygen with little effect on the functional capacity of the respiratory system (2). Contrary to the hypothesis, reductions in Pdi,tw and oesophageal twitch pressure (Poes,tw, a measure for global inspiratory muscle fatigue) were significantly larger (student`s t test, p<0.05) after the 15TT (Pdi,tw: -25.4±6.9%, Poes,tw: -25.8±7.5%) compared to the 30TT (-19.2±9.9%, -13.8±12.1%) thus not implicating a threshold of diaphragmatic or global inspiratory muscle fatigue during TTs. The observed difference in inspiratory muscle fatigue is likely the result of the significantly higher exercise intensity in the 15TT (91±1% VO2max) compared to the 30TT (86±4% VO2max) resulting in a higher ventilation during the 15TT (~9%, p<0.05) and thus greater inspiratory muscle work, i.e. inspiratory diaphragmatic and oesophageal pressure-time-product (PTPdi: ~23%, p<0.05; PTPoes: ~16%, p=0.07) and work of breathing (~26%, p<0.05). Moreover, global inspiratory muscle fatigue was significantly larger after exhaustive volitional hyperpnoea (decrease in Pm,tw: -34±9.4%) compared to Poes,tw after either TT. In summary, we conclude that the high level of ventilation achieved during whole-body exercise does not stress the inspiratory muscles to the point where a threshold of fatigue is reached. Thus, to which extent the level of inspiratory muscle fatigue contributes to exercise limitation, needs further investigation.